NVP-2, in combination with Orlistat, represents a promising therapeutic strategy for acute myeloid leukemia - Qing Zhu; Jia Cheng; Yuqing Gao; Zimu Zhang; Jian Pan; Xin Su; Danhong Fei; Linbo Cai; Juanjuan Yu; Yanling Chen; Wanyan Jiao; Di Wu; et al. (Cancer Biology & Therapy)
Cell cycle dysregulation and the corresponding metabolic reprogramming play significant roles in tumor development and progression. CDK9, a kinase that regulates gene transcription and cell cycle, also induces oncogene transcription and abnormal cell cycle in AML cells. The function of CDK9 for gene regulation in AML cells requires further exploration. In this study, we knocked down the CDK9 to investigate its effects on the growth and survival of AML cells. Through RNA-seq analysis, we identified that in U937 cells CDK9 regulates numerous genes involved in proliferation and apoptosis, including mTOR, SREBF1, and Bcl-2. Furthermore, our results demonstrated that both CDK9 and FASN are crucial for the proliferation and survival of Kasumi-1 and U937 cells. Mechanistically, MCL1, c-Myc, and Akt/mTOR/SREBF1 may be critical factors and pathways in the combined therapy of NVP-2 and Orlistat. In summary, our study revealed that CDK9 and FASN are vital for maintaining AML cell survival and proliferation. Treatment with NVP-2 and Orlistat may be a promising clinical candidate for patients with AML.